PERKEMBANGAN SOSIAL ANAK USIA DINI SEBAGAI BIBIT UNTUK MASA DEPAN BANGSA - Farida Mayar (AT-TA'LIM, 2013)
Children social development is determined by the child’s individual, the roles of parents, social environment, and Kindegarten.  There is a strong relationship between the ability to socialize and the happiness in the childhood.   The child’s ability to adapt to the environment and the acceptance of environment as well as positive experiences in their social activities serve as crucial factor to reach fun and successful life in the future.  Social development is actually a maturity achievement in the social relationship.  It can also refer to learning process to adapt to the social norm, moral and tradition:  Diffusing into an interrelationship unit to communicate and cooperate.  Social development in a family is also influenced by several factors such as status of the family, unity of family, attitudes, and  parents’ habit. Copyright © 2013 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v20i3.43